2020
DOI: 10.1213/ane.0000000000005081
|View full text |Cite
|
Sign up to set email alerts
|

American Society for Enhanced Recovery and Perioperative Quality Initiative Joint Consensus Statement on the Role of Neuromonitoring in Perioperative Outcomes: Cerebral Near-Infrared Spectroscopy

Abstract: Some neurological complications following surgery have been related to a mismatch in cerebral oxygen supply and demand that may either lead to more subtle changes of brain function or overt complications like stroke or coma. Discovery of a perioperative neurological complication may be outside the treatment window, thereby making prevention an important focus. Early commercial devices used differential spectroscopy to measure relative changes from baseline of 2 chromophores: oxy- and deoxyhemoglobin. It was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 79 publications
1
41
0
4
Order By: Relevance
“…In der Summe scheinen aber dennoch die positiven Effekte zu überwiegen. Entsprechend stellt die POQI -wenn auch nur mit einem schwachen Empfehlungsgrad -in ihren aktuellen Empfehlungen fest, dass mithilfe der Zerebraloxymetrie gesteuerte Algorithmen geeignet sind, die Dauer eines Intensivaufenthalts zu verkürzen [7].…”
Section: Zu 3 Wie In Dieser Ausgabe Von Derunclassified
See 1 more Smart Citation
“…In der Summe scheinen aber dennoch die positiven Effekte zu überwiegen. Entsprechend stellt die POQI -wenn auch nur mit einem schwachen Empfehlungsgrad -in ihren aktuellen Empfehlungen fest, dass mithilfe der Zerebraloxymetrie gesteuerte Algorithmen geeignet sind, die Dauer eines Intensivaufenthalts zu verkürzen [7].…”
Section: Zu 3 Wie In Dieser Ausgabe Von Derunclassified
“…Wir müssen wahrscheinlich damit leben, dass es -insbesondere im Bereich des Monitorings und der Akutdiagnostik in Anästhesie und Intensivmedizin -außerordentlich schwer ist, Evidenz auch für das Augenscheinliche zu generieren und dass, aufgrund des Neudeutsch auch als "Confounding" bezeichneten "Hintergrundrauschens" aus schwer stratifizierbaren chirurgischen Einflussfaktoren auf das Outcome [4], sekundären, in Studien nahezu nie erfassten Variablen wie der Qualität der postoperativen Versorgung [5], und der biologischen Variabilität der behandelten Patienten [6], in absehbarer Zeit auch keine den Kriterien der EBM genügenden Nachweise erbracht werden können! Dennoch stellen sich im Hinblick auf den klinischen Einsatz der Zerebraloxymetrie und die Messung der regionalen zerebralen Sauerstoffsättigung ("regional cerebral oxygen saturation", rScO2) mithilfe der NIRS eine Reihe von Fragen, um die keineswegs trivialen Kosten für den Einsatz dieser Technologie zu rechtfertigen: [7]. Dies bedingt, dass auch die Ergebnisse von Studien mit Geräten eines Herstellers nicht notwendigerweise auf die eines anderen Herstellers übertragen werden können, und macht es notwendig, für jedes auf dem Markt befindliche Zerebraloxymeter spezifische Norm-und Grenzwerte zu ermitteln [9].…”
unclassified
“…First, we can noninvasively measure cerebral oxygenation (ScO 2 ) by NIRS. Currently, ScO 2 monitoring is widely used to detect cerebral perfusion abnormalities in cardiac and non‐cardiac surgeries 6,7 . In addition, it was reported that the intraoperative decrease in ScO 2 was related to postoperative delirium and/or cognitive dysfunction, especially in cardiac surgery 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ScO 2 monitoring is widely used to detect cerebral perfusion abnormalities in cardiac and non‐cardiac surgeries 6,7 . In addition, it was reported that the intraoperative decrease in ScO 2 was related to postoperative delirium and/or cognitive dysfunction, especially in cardiac surgery 6,7 . Some different principals are adopted in commercially available NIRS monitoring: the Modified Beer–Lambert law (MBL) and spatial‐resolved spectroscopy (SRS) have been the representative methods 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation